Enhanced cytotoxicity of a Pseudomonas Exotoxin A based immunotoxin against prostate cancer by addition of the endosomal escape enhancer SO1861 - Masilamani, Anie P.; Huber, Nathalie; Nagl, Constanze; Dettmer-Monaco, Viviane; Monaco, Gianni; Wolf, Isis; Schultze-Seemann, Susanne; Taromi, Sanaz; Gratzke, Christian; Fuchs, Hendrik; Wolf, Philipp (Frontiers in Pharmacology, 2023)
Immunotoxins consist of an antibody or antibody fragment that binds to a specific cell surface structure and a cytotoxic domain that kills the cell after cytosolic uptake. Pseudomonas Exotoxin A (PE) based immunotoxins directed against a variety of tumor entities have successfully entered the clinic. PE possesses a KDEL-like motif (REDLK) that enables the toxin to travel from sorting endosomes via the KDEL-receptor pathway to the endoplasmic reticulum (ER), from where it is transported into the cytosol. There, it ADP-ribosylates the eukaryotic elongation factor 2, resulting in ribosome inhibition and finally apoptosis. One major problem of immunotoxins is their lysosomal degradation causing the need for much more immunotoxin molecules than finally required for induction of cell death. The resulting dose limitations and substantially increased side effects require new strategies to achieve improved cytosolic uptake. Here we generated an immunotoxin consisting of a humanized single chain variable fragment (scFv) targeting the prostate specific membrane antigen (PSMA) and the de-immunized PE variant PE24mut. This immunotoxin, hD7-1(VL-VH)-PE24mut, showed high and specific cytotoxicity in PSMA-expressing prostate cancer cells. We deleted the REDLK sequence to prevent transport to the ER and achieve endosomal entrapment. The cytotoxicity of this immunotoxin, hD7-1(VL-VH)-PE24mutΔREDLK, was greatly reduced. To restore activity, we added the endosomal escape enhancer SO1861 and observed an up to 190,000-fold enhanced cytotoxicity corresponding to a 57-fold enhancement compared to the initial immunotoxin with the REDLK sequence. A biodistribution study with different routes of administration clearly showed that the subcutaneous injection of hD7-1(VL-VH)-PE24mutΔREDLK in mice resulted in the highest tumor uptake. Treatment of mice bearing prostate tumors with a combination of hD7-1(VL-VH)-PE24mutΔREDLK plus SO1861 resulted in inhibition of tumor growth and enhanced overall survival. The endosomal entrapment of non-toxic anti-PSMA immunotoxins followed by enhanced endosomal escape by SO1861 provides new therapeutic options in the management of prostate cancer and could lead to enhanced antitumor activity and reduced off-tumor side effects.